Ru (at) t-ZrO2 / C electrocatalyst and preparation method thereof

Ru@t-ZrO2/C electrocatalysts were prepared by solvothermal and in-situ reduction methods, which solved the problems of low utilization of active sites and weak electron transfer performance in Ru-based MOF catalysts. This achieved high dispersion of Ru and improved the structural stability of the catalyst, thereby increasing the efficiency of the electrocatalytic hydrogen evolution reaction.

CN121065739APending Publication Date: 2025-12-05SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511213003.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

In existing Ru-based MOF catalysts, the presence of Ru nanoparticles leads to low utilization of active sites, weak electron transfer performance, and poor catalyst stability, which limits their application in the hydrogen evolution reaction.

Method used

UiO-66 metal-organic framework precursor was synthesized by solvothermal method, and ruthenium metal active component was efficiently loaded into the three-dimensional ordered porous structure of UiO-66 by in-situ reduction method. Then, it was subjected to temperature-controlled heat treatment under argon atmosphere to form Ru@t-ZrO2/C electrocatalyst.

Benefits of technology

This method achieves high dispersion and confined growth of Ru, improves the structural stability and electron transfer performance of the catalyst, and enhances the efficiency of the electrocatalytic hydrogen evolution reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121065739A_ABST
    Figure CN121065739A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrocatalysts, in particular to a Ru t-ZrO2 / C electrocatalyst and a preparation method thereof.The preparation method includes the steps that zirconium tetrachloride, terephthalic acid, N, N-dimethylformamide and formic acid are put into a polytetrafluoroethylene lining to be subjected to a solvothermal reaction, and after the temperature is cooled to the room temperature, centrifugal washing and vacuum drying are conducted through DMF and methyl alcohol to obtain UiO-66 powder; secondly, dispersing the UiO-66 powder in methanol, adding ruthenium trichloride, stirring, centrifugally washing with methanol, and drying in vacuum to obtain a precursor Ru-UiO-66; and finally, sintering the precursor Ru (at) UiO-66 in a tubular furnace under an argon condition to obtain the Ru (at) t-ZrO2 / C electrocatalyst. According to the present invention, the strong interaction between the Zr-Ru bimetallic sites is combined with the strong conductive structure formed by ZrO2 and the carbon substrate, such that the prepared electrocatalyst has characteristics of low loading amount of the noble metal Ru cluster, excellent structure stability, high active site utilization rate, and efficient electron transfer with the MOFs carrier so as to show the efficient acid-base system electrocatalytic property;
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of electrocatalysts, in particular to a Ru@t-ZrO2 / C electrocatalyst and a preparation method thereof. BACKGROUND

[0002] With the large consumption of fossil fuels, global energy shortage and environmental problems are becoming increasingly serious. Therefore, finding clean, sustainable and environmentally friendly green sustainable energy has become a hot research topic. Hydrogen energy is considered as the most potential sustainable clean energy due to its high energy density, zero emission and renewable characteristics, which has attracted extensive research interest worldwide. Electrolysis of water to produce hydrogen is an important direction in current green hydrogen production technology, and the core is to decompose water into hydrogen and oxygen through electrocatalytic reaction. Among them, the electrocatalytic hydrogen evolution reaction (HER) is one of the key technologies for electrolysis of water to produce hydrogen. Although the noble metal platinum (Pt) based material is currently the most effective HER electrocatalyst, its high cost and scarcity seriously limit its large-scale commercial application.

[0003] Ruthenium (Ru) as a relatively low-cost catalyst shows good activity in alkaline hydrogen evolution reaction (HER) and is expected to replace platinum (Pt) based catalysts. However, its weak water adsorption capacity limits the water decomposition and mass transfer efficiency. In recent years, metal-organic frameworks (MOFs) as a new type of porous crystalline material have attracted much attention due to their high specific surface area, structural adjustability and rich pore structure. However, MOFs usually have poor structural stability, low electrical conductivity and are easily degraded in electrochemical environment, which limits their direct application in hydrogen evolution reaction. In the prior art, Ru is introduced into the structure of MOFs to realize high dispersion anchoring of metals by using the regular pores and rich coordination sites of MOFs, so as to construct efficient and high-atom-utilization catalytic active centers. However, the metal Ru in the Ru-based MOF catalyst mainly exists in the form of nanoparticles (NPs), which further leads to reduced active site utilization, weakened electron transfer performance between the catalyst and the MOF support, and decreased stability of the catalyst. SUMMARY

[0004] The present application aims to provide a Ru@t-ZrO2 / C electrocatalyst and a preparation method thereof. The electrocatalyst has low noble metal-loaded Ru clusters, good structural stability, high active site utilization, and strong electron transfer performance with the MOF support.

[0005] The present application is realized by the following technical solutions:

[0006] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, comprising the following steps:

[0007] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC are weighed according to a molar ratio of (0.8-1.2):1, dissolved in 40-60 mL of N,N dimethylformamide DMF to form an A solution, 3-5 mL of formic acid is added to the A solution to form a B solution and ultrasonic treatment is performed;

[0008] S2: The B solution is placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, hydrothermal reaction is performed at 110-130 DEG C, then cooled to room temperature to obtain a product C, the product C is washed, centrifuged using a methanol / DMF mixed solvent in a volume ratio of (1-2):1, and dried under vacuum to obtain a UiO-66 powder;

[0009] S3: 200 mg of the UiO-66 powder is dispersed in 30-40 mL of methanol to form a D solution, 0.1-0.3 mmol of ruthenium trichloride powder is dispersed in the D solution, stirring is performed at room temperature to obtain a solution E, the solution E is washed, centrifuged using a methanol solution, and dried under vacuum to obtain a precursor Ru@UiO-66;

[0010] S4: The precursor Ru@UiO-66 is heated to 600-800 DEG C in a tube furnace filled with argon for 2-3 h, then cooled to 300 DEG C, and naturally cooled to room temperature to obtain a Ru@t-ZrO2 / C electrocatalyst.

[0011] Further, the ultrasonic treatment in step S1 is performed for 20-40 min.

[0012] Further, the hydrothermal reaction in step S2 is performed for 10-13 h.

[0013] Further, the vacuum drying in steps S2 and S3 is performed at a temperature of 60-80 DEG C for 10-14 h.

[0014] Further, the centrifugation in steps S2 and S3 is performed at a speed of 3000-5000 r / min for 5-10 min, and repeated 3-5 times.

[0015] Further, the stirring in step S3 is performed at a speed of 600-800 r / min for 12-36 h at room temperature of 20-30 DEG C.

[0016] Further, the heating and cooling rates in step S4 are 5-10 DEG C / min.

[0017] The application further provides a Ru@t-ZrO2 / C electrocatalyst, which is in a nanoparticle structure, and the noble metal Ru is loaded on a carbon substrate of ZrO2 in the form of a cluster.

[0018] Compared with the prior art, the present application has the following beneficial effects:

[0019] The present application first synthesizes a UiO-66 metal organic framework (MOF) precursor by a solvothermal method, which has the advantages of complete crystal grain development, small and uniform particle size, and regular spherical morphology, and then efficiently loads a ruthenium (Ru) metal active component in the three-dimensional ordered pore structure of the UiO-66 by an in-situ reduction method, realizing high dispersion and limited growth of the Ru. The process is simple to operate, mild in conditions, and good in repeatability, does not require complex equipment, and is easy to accurately control, which is conducive to large-scale production. Finally, the obtained Ru@UiO-66 precursor is subjected to temperature control heat treatment in a tube furnace under an argon atmosphere. The pyrolysis process not only carbonizes the organic ligand to form a conductive carbon skeleton, significantly improving the electrical conductivity of the material, but also promotes the conversion of Zr clusters into t-ZrO2 with high stability, and realizes strong metal-support interaction (SMSI) between Ru nanoparticles and the t-ZrO2 / C carrier. The entire heat treatment process is simple, only needs to set the temperature rising program and keep warm in an inert atmosphere, has strong experimental repeatability, and is suitable for large-scale preparation.

[0020] The Ru@t-ZrO2 / C catalyst prepared by the present application has a high specific surface area, rich pore structure, and excellent electrical conductivity. The Ru metal is efficiently loaded in the three-dimensional ordered pore structure of the ZrO2 / C carrier, realizing high dispersion and limited growth of the Ru clusters. More importantly, ZrO2 has strong Zr-OH* affinity characteristics, resulting in rapid hydrolysis dissociation capacity, thereby providing abundant H*; meanwhile, the Ru clusters promote rapid overflow of H* under the advantages of high active site number and strong electronic transmission with the carrier. Therefore, through effective regulation of the Zr-Ru metal-support interaction, the catalyst Ru@t-ZrO2 / C realizes optimization of the electronic structure and stability of the active sites, significantly improving its electrocatalytic hydrogen evolution reaction (HER) performance. BRIEF DESCRIPTION OF DRAWINGS

[0021] Figure 1 is an X-ray diffraction analysis diagram of the UiO-66 prepared in Example 2;

[0022] Figure 2 is an SEM diagram of the UiO-66 prepared in Example 2;

[0023] Figure 3 is an X-ray diffraction analysis diagram of the Ru 0.1 @t-ZrO2 / C-700 prepared in Example 2;

[0024] Figure 4 is an SEM diagram of the Ru 0.1 @t-ZrO2 / C-700 prepared in Example 2;

[0025] Figure 5 Ru@t-ZrO2 / C-700 prepared in Example 2 0.1 TEM image of t-ZrO2 / C-700;

[0026] Figure 6 Ru@t-ZrO2 / C-700 prepared in Example 2 0.1 Linear sweep voltammetry curve of t-ZrO2 / C-700 for hydrogen evolution in alkaline condition;

[0027] Figure 7 Ru@t-ZrO2 / C-700 prepared in Example 2 0.1 Linear sweep voltammetry curve of t-ZrO2 / C-700 for hydrogen evolution in acidic condition. DETAILED DESCRIPTION

[0028] The present application is further described in detail by the following specific examples, which are explanatory rather than limiting.

[0029] Example 1

[0030] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, specifically comprising:

[0031] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 0.8:1, dissolved in 40 mL of N,N dimethylformamide DMF to form an A solution, 3 mL of formic acid was added to the A solution to form a B solution and was subjected to ultrasonic treatment for 40 min;

[0032] S2: The B solution was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and was subjected to hydrothermal reaction at 110°C for 13 h, and then cooled to room temperature to obtain a product C, the product C was washed with a mixed solvent of methanol and DMF in a volume ratio of 2:1, centrifuged at a speed of 5000 r / min for 5 min, repeated 4 times, and vacuum dried at 60°C for 14 h to obtain UiO-66 powder;

[0033] S3: 200 mg of the UiO-66 powder was dispersed in 40 mL of methanol to form a D solution, 0.1 mmol of ruthenium trichloride powder was dispersed in the D solution, stirred at a speed of 800 r / min at room temperature of 20°C for 12 h to obtain a solution E, the solution E was washed with 20 mL of methanol solution, centrifuged at a speed of 4000 r / min for 10 min, repeated 4 times, and vacuum dried at 60°C for 10 h to obtain a precursor Ru 0.1 @UiO-66;

[0034] S4: 150 mg of the precursor Ru 0.1UiO-66 was heated in a tube furnace filled with argon from room temperature to 600℃ at a heating rate of 10℃ / min, and then kept for 2h, and then cooled to 300℃ at a cooling rate of 10℃ / min, and then naturally cooled to room temperature to obtain Ru 0.1 @t-ZrO2 / C-600 electrocatalyst.

[0035] Example 2

[0036] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0037] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50mL of N,N dimethylformamide DMF to form an A solution, 3.6mL of formic acid was added to the A solution to form a B solution and was subjected to ultrasonic treatment for 30min;

[0038] S2: The B solution was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was carried out at 120℃ for 12h, and then cooled to room temperature to obtain a product C, the product C was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000r / min for 10min, repeated for 3 times, and vacuum dried at 80℃ for 10h to obtain UiO-66 powder;

[0039] S3: 200mg of the UiO-66 powder was dispersed in 40mL of methanol to form a D solution, 0.1mmol of ruthenium trichloride powder was dispersed in the D solution, and the solution was stirred at a speed of 700r / min at room temperature for 24h to obtain a solution E, the solution E was washed with 20mL of methanol, centrifuged at a speed of 4000r / min for 10min, repeated for 3 times, and vacuum dried at 80℃ for 10h to obtain a precursor Ru 0.1 @UiO-66;

[0040] S4: 150mg of the precursor Ru 0.1 @UiO-66 was heated in a tube furnace filled with argon from room temperature to 700℃ at a heating rate of 10℃ / min, and then kept for 2h, and then cooled to 300℃ at a cooling rate of 10℃ / min, and then naturally cooled to room temperature to obtain Ru 0.1 @t-ZrO2 / C-700 electrocatalyst.

[0041] Example 3

[0042] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0043] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1.2:1, dissolved in 60 mL of N,N-dimethylformamide DMF to form solution A, 5 mL of formic acid was added to solution A to form solution B and was subjected to ultrasonic treatment for 20 min;

[0044] S2: The solution B was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was performed at 130 DEG C for 10 h, and then cooled to room temperature to obtain product C, which was washed with a mixed solvent of methanol and DMF in a volume ratio of 1.5:1, centrifuged at a speed of 3000 r / min for 10 min, repeated 3 times, and vacuum dried at 70 DEG C for 12 h to obtain UiO-66 powder;

[0045] S3: 200 mg of UiO-66 powder was dispersed in 30 mL of methanol to form solution D, 0.1 mmol of ruthenium trichloride powder was dispersed in solution D, and solution E was obtained by stirring at a speed of 600 r / min for 36 h at room temperature of 30 DEG C, solution E was washed with 20 mL of methanol, centrifuged at a speed of 3000 r / min for 10 min, repeated 3 times, and vacuum dried at 70 DEG C for 12 h to obtain precursor Ru 0.1 @UiO-66;

[0046] S4: 150 mg of precursor Ru 0.1 @UiO-66 was heated in a tube furnace filled with argon at a heating rate of 5 DEG C / min from room temperature to 800 DEG C and kept for 3 h, then cooled to 300 DEG C at a cooling rate of 5 DEG C / min, and naturally cooled to room temperature to obtain Ru 0.1 @t-ZrO2 / C-800 electrocatalyst.

[0047] Example 4

[0048] A method for preparing a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0049] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50 mL of N,N-dimethylformamide DMF to form solution A, 3.6 mL of formic acid was added to solution A to form solution B and was subjected to ultrasonic treatment for 30 min;

[0050] S2: The solution B was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was performed at 120 DEG C for 12 h, and then cooled to room temperature to obtain product C, which was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000 r / min for 8 min, repeated 5 times, and vacuum dried at 80 DEG C for 12 h to obtain UiO-66 powder;

[0051] S3: 200mg of UiO-66 powder was dispersed in 40mL of methanol to form a D solution, 0.2mmol of ruthenium trichloride powder was dispersed in the D solution, and a solution E was obtained by stirring at a speed of 800r / min at room temperature for 24h, the solution E was washed with 20mL of methanol solution, centrifuged at a speed of 4000r / min for 8min, repeated 5 times, and vacuum dried at 80℃ for 12h to obtain the precursor Ru 0.2 @UiO-66;

[0052] S4: 150mg of the precursor Ru 0.2 @UiO-66 was heated in an argon-filled tube furnace at a heating rate of 8℃ / min from room temperature to 600℃ and kept for 2.5h, then cooled to 300℃ at a cooling rate of 8℃ / min, and naturally cooled to room temperature to obtain Ru 0.2 @t-ZrO2 / C-600 electrocatalyst.

[0053] Example 5

[0054] A method for preparing a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0055] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50mL of N,N dimethylformamide DMF to form a A solution, 3.6mL of formic acid was added to the A solution to form a B solution and was ultrasonically treated for 30min;

[0056] S2: The B solution was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and hydrothermal reaction was carried out at 120℃ for 12h, then cooled to room temperature to obtain product C, the product C was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain UiO-66 powder;

[0057] S3: 200mg of UiO-66 powder was dispersed in 40mL of methanol to form a D solution, 0.2mmol of ruthenium trichloride powder was dispersed in the D solution, and a solution E was obtained by stirring at a speed of 800r / min at room temperature for 24h, the solution E was washed with 20mL of methanol solution, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain the precursor Ru 0.2 @UiO-66;

[0058] S4: 150mg of the precursor Ru 0.2UiO-66 was heated in a tube furnace filled with argon from room temperature to 700℃ at a heating rate of 10℃ / min, and then kept for 2h, and then cooled to 300℃ at a cooling rate of 10℃ / min, and then naturally cooled to room temperature to obtain Ru 0.2 @t-ZrO2 / C-700 electrocatalyst.

[0059] Example 6

[0060] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0061] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50mL of N,N dimethylformamide DMF to form solution A, 3.6mL of formic acid was added to solution A to form solution B and was subjected to ultrasonic treatment for 30min;

[0062] S2: The solution B was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was carried out at 120℃ for 12h, and then cooled to room temperature to obtain product C, the product C was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000r / min for 10min, repeated 5 times, and vacuum dried at 80℃ for 10h to obtain UiO-66 powder;

[0063] S3: 200mg of UiO-66 powder was dispersed in 40mL of methanol to form solution D, 0.2mmol of ruthenium trichloride powder was dispersed in solution D, and stirring was carried out at a speed of 800r / min at room temperature for 24h to obtain solution E, solution E was washed with 20mL of methanol, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain the precursor Ru 0.2 @UiO-66;

[0064] S4: 150mg of the precursor Ru 0.2 @UiO-66 was heated in a tube furnace filled with argon from room temperature to 800℃ at a heating rate of 10℃ / min, and then kept for 2h, and then cooled to 300℃ at a cooling rate of 10℃ / min, and then naturally cooled to room temperature to obtain Ru 0.2 @t-ZrO2 / C-800 electrocatalyst.

[0065] Example 7

[0066] A preparation method of a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0067] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50 mL of N,N-dimethylformamide DMF to form solution A, 3.6 mL of formic acid was added to solution A to form solution B and was subjected to ultrasonic treatment for 30 min;

[0068] S2: The solution B was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was carried out at 120 DEG C for 12 h, and then cooled to room temperature to obtain product C, which was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000 r / min for 10 min, repeated for 3 times, and vacuum dried at 80 DEG C for 10 h to obtain UiO-66 powder;

[0069] S3: 200 mg of UiO-66 powder was dispersed in 40 mL of methanol to form solution D, 0.3 mmol of ruthenium trichloride powder was dispersed in solution D, and solution E was obtained by stirring at a speed of 800 r / min for 24 h at room temperature, solution E was washed with 20 mL of methanol, centrifuged at a speed of 4000 r / min for 10 min, repeated for 3 times, and vacuum dried at 80 DEG C for 10 h to obtain precursor Ru 0.3 @UiO-66;

[0070] S4: 150 mg of precursor Ru 0.3 @UiO-66 was heated in an argon-filled tube furnace at a heating rate of 10 DEG C / min from room temperature to 600 DEG C and kept for 2 h, then cooled to 300 DEG C at a cooling rate of 10 DEG C / min, and naturally cooled to room temperature to obtain Ru 0.3 @t-ZrO2 / C-600 electrocatalyst.

[0071] Example 8

[0072] A method for preparing a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0073] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50 mL of N,N-dimethylformamide DMF to form solution A, 3.6 mL of formic acid was added to solution A to form solution B and was subjected to ultrasonic treatment for 30 min;

[0074] S2: The solution B was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and a hydrothermal reaction was carried out at 120 DEG C for 12 h, and then cooled to room temperature to obtain product C, which was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000 r / min for 10 min, repeated for 3 times, and vacuum dried at 80 DEG C for 10 h to obtain UiO-66 powder;

[0075] S3: 200mg of UiO-66 powder was dispersed in 40mL of methanol to form a D solution, 0.3mmol of ruthenium trichloride powder was dispersed in the D solution, and the solution was stirred at a speed of 800r / min at room temperature for 24h to obtain solution E, the solution E was washed with 20mL of methanol solution, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain the precursor Ru 0.3 @UiO-66;

[0076] S4: 150mg of the precursor Ru 0.3 @UiO-66 was heated in an argon-filled tube furnace at a heating rate of 10℃ / min from room temperature to 700℃ and kept for 2h, then cooled to 300℃ at a cooling rate of 10℃ / min, and naturally cooled to room temperature to obtain Ru 0.3 @t-ZrO2 / C-700 electrocatalyst.

[0077] Example 9

[0078] A method for preparing a Ru@t-ZrO2 / C electrocatalyst, specifically:

[0079] S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC were weighed according to a molar ratio of 1:1, dissolved in 50mL of N,N dimethylformamide DMF to form a A solution, 3.6mL of formic acid was added to the A solution to form a B solution and was ultrasonically treated for 30min;

[0080] S2: The B solution was placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and hydrothermal reaction was carried out at 120℃ for 12h, then cooled to room temperature to obtain product C, the product C was washed with a mixed solvent of methanol and DMF in a volume ratio of 1:1, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain UiO-66 powder;

[0081] S3: 200mg of UiO-66 powder was dispersed in 40mL of methanol to form a D solution, 0.3mmol of ruthenium trichloride powder was dispersed in the D solution, and the solution was stirred at a speed of 800r / min at room temperature for 24h to obtain solution E, the solution E was washed with 20mL of methanol solution, centrifuged at a speed of 4000r / min for 10min, repeated 3 times, and vacuum dried at 80℃ for 10h to obtain the precursor Ru 0.3 @UiO-66;

[0082] S4: 150mg of the precursor Ru 0.3@UiO-66 was heated from room temperature to 800℃ in an argon-filled tube furnace at a heating rate of 10℃ / min and held for 2 hours, then cooled to 300℃ at a cooling rate of 10℃ / min and allowed to cool naturally to room temperature to obtain Ru. 0.3 @t-ZrO2 / C-800 electrocatalyst.

[0083] The UiO-66 precursor prepared in Example 2 was selected for characterization and analysis. Figure 1 The X-ray diffraction (XRD) pattern shows that the diffraction peak positions of this precursor perfectly match the simulated XRD pattern of standard UiO-66, indicating that it has the same crystal structure as UiO-66 and good crystallinity. Figure 2 The scanning electron microscope (SEM) images show that the UiO-66 precursor crystals are well-developed, small in size, uniformly distributed, and have a regular morphology. The combined XRD and SEM analysis results indicate that UiO-66 has been successfully prepared and has good morphology and crystallization properties.

[0084] Ru prepared in Example 2 0.1 X-ray diffraction (XRD) analysis was performed on the @t-ZrO2 / C-700 catalyst. Figure 3 As shown, the catalyst Ru after high-temperature pyrolysis 0.1 The XRD diffraction peaks of @t-ZrO2 / C-700 correspond to the (10 1), (1 1 0), (1 1 2), and (2 1 1) crystal planes of t-ZrO2 (PDF#79-1770), indicating that the catalyst support is t-ZrO2 / C. Notably, no diffraction peaks for the hexagonal phase Ru (PDF#06-0663) were observed in the XRD diffraction peaks. This is attributed to the fact that Ru exists in the form of clusters, and its small size and high dispersion in the three-dimensional ordered pores of t-ZrO2 / C.

[0085] Further observation of the catalyst morphology was conducted using scanning electron microscopy (SEM), such as... Figure 4 As shown, the results show Ru 0.1 The @t-ZrO2 / C-700 catalyst has well-developed, regular morphology, and uniform distribution of crystal grains, with no obvious agglomeration, indicating that it has good structural stability and uniformity.

[0086] High-resolution transmission electron microscopy (HRTEM) analysis further confirmed the above conclusions, such as... Figure 5 As shown, Ru 0.1The lattice fringe spacing of 0.295 nm and 0.299 nm in the HRTEM image of t-ZrO2 / C-700 corresponds to the (101) plane of t-ZrO2, further verifying the crystal structure of t-ZrO2 in the support. However, no obvious Ru lattice fringes were observed in the HRTEM image, again indicating that Ru was highly dispersed in the form of ultrafine clusters within the pores of the support without significant aggregation.

[0087] In summary, the XRD, SEM and HRTEM characterization results confirm each other, and fully prove that Ru 0.1 @In the t-ZrO2 / C-700 catalyst, Ru is anchored on the t-ZrO2 / C support in the form of ultrafine clusters and is highly dispersed, has excellent structural stability, is conducive to exposing more active sites, and has potential high-efficiency catalytic performance.

[0088] As Figure 6 shown, in an alkaline electrolyte of 1M KOH, when the current density of the catalyst Ru 0.1 @t-ZrO2 / C-700 reached 10 mA cm -2 , the overpotential was only 16 mV. This indicates that the catalyst has excellent hydrogen evolution reaction (HER) performance in an alkaline environment. As Figure 7 shown, in an acidic electrolyte of 0.5M H2SO4, when the current density reached 10 mA cm -2 , the overpotential was 53 mV, also at a low level, indicating that it also has good HER catalytic activity in an acidic medium. In summary, the Ru 0.1 @t-ZrO2 / C-700 catalyst exhibits excellent hydrogen evolution performance in a wide pH range.

Claims

1. A method for preparing a Ru@t-ZrO2 / C electrocatalyst, characterized in that, The method comprises the following steps: S1: Zirconium tetrachloride ZrCl4 and terephthalic acid H2BDC are weighed according to a molar ratio of (0.8-1.2):1, dissolved in 40-60 mL of N,N-dimethylformamide DMF to form an A solution, 3-5 mL of formic acid is added to the A solution to form a B solution and ultrasonic treatment is performed; S2: The B solution is placed in a hydrothermal kettle containing a polytetrafluoroethylene liner, and hydrothermal reaction is performed at 110-130 DEG C, and then cooled to room temperature to obtain a product C, the product C is washed and centrifuged using a methanol-DMF mixed solvent with a volume ratio of (1-2):1, and the UiO-66 powder is obtained under vacuum drying conditions; S3: 200 mg of the UiO-66 powder is dispersed in 30-40 mL of methanol to form a D solution, 0.1-0.3 mmol of ruthenium trichloride powder is dispersed in the D solution, and a solution E is obtained by stirring at room temperature, the solution E is washed and centrifuged using a methanol solution, and the precursor Ru@UiO-66 is obtained under vacuum drying conditions; S4: The precursor Ru@UiO-66 is heated to 600-800 DEG C in an argon-filled tube furnace for 2-3 h, and then cooled to 300 DEG C, and the Ru@t-ZrO2 / C electrocatalyst is obtained by natural cooling to room temperature.

2. The preparation method of Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The ultrasonic treatment in step S1 is performed for 20-40 min.

3. The method for preparing a Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The hydrothermal reaction in step S2 is performed for 10-13 h.

4. The method for preparing a Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The vacuum drying in steps S2 and S3 is performed at a temperature of 60-80 DEG C for 10-14 h.

5. The method for preparing a Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The centrifugation in steps S2 and S3 is performed at a speed of 3000-5000 r / min for 5-10 min, and the operation is repeated for 3-5 times.

6. The method for preparing a Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The stirring in step S3 is performed at a speed of 600-800 r / min for 12-36 h at room temperature of 20-30 DEG C.

7. The method for preparing a Ru@t-ZrO2 / C electrocatalyst according to claim 1, characterized in that, The heating and cooling rates in step S4 are 5-10 DEG C / min.

8. A Ru@t-Zr02 / C electrocatalyst prepared according to the method of any one of claims 1 to 7, characterized in that, The Ru@t-ZrO2 / C electrocatalyst is in a nanoparticle structure, and the noble metal Ru is loaded on the carbon substrate of ZrO2 in the form of clusters.